The Arousal Effect of Exclusionary and Inclusionary Situations on Social Affiliation Motivation and Its Subsequent Influence on Prosocial Behavior - Cuadrado, Esther; Tabernero, Carmen; Hidalgo-Muñoz, Antonio R.; Luque, Bárbara; Castillo-Mayén, Rosario (Frontiers in Psychology, 2021)
Given the negative costs of exclusion and the relevance of belongingness for humans, the experience of exclusion influences social affiliation motivation, which in turn is a relevant predictor of prosocial behavior. Skin conductance is a typical measure of the arousal elicited by emotions. Hence, we argued that both inclusion and exclusion will increase skin conductance level due to the increase of either positive affect or anger affects, respectively. Moreover, we argued that emotional arousal is also related to social affiliation motivation and prosocial behavior. A total of 48 students were randomly allocated to either an inclusionary or exclusionary condition and their skin conductance levels were recorded during an experiment in which they completed an online questionnaire and played the game “Cyberball.” Results indicated that (a) individuals who perceived high exclusion felt angrier than individuals perceiving high inclusion, who feel positive affect; (b) no differences were evidenced in terms of skin conductance between exclusion and inclusion situations; (c) over-aroused individuals were less motivated to affiliate; and (d) individuals with lower affiliation motivation behaved in a less prosocial way. The results were congruent to the argument that behaving prosocially may be a way to gain the desired affiliation.